Institutional Reform for Investment and Growth in South Eastern Europe - Broadman, Harry (World Bank, Washington, DC, 2017)
This study analyses the institutional impediments to investment and growth in SEE and suggests ‘second generation’ policy reforms to ease these constraints. Chapter one reviews the recent trends in the economies of the eight countries that comprise the region (SEE8) and their prospects for international and intra-regional integration. It conveys the message that a favorable institutional framework for domestic and foreign investment is essential to achieve sustainable growth in SEE. The chapter presents the scope, methodology, and the approach the study undertakes for assessing the role of key market institutions in SEE business development. The analysis utilizes not only traditional, official data from the eight countries to assess the characteristics, trends and relationships between these institutions, but also employs data from a set of 40 original enterprise-level business case studies carried out in each of the eight countries and the two rounds of the Business Environment and Enterprise Performance Survey (BEEPS) conducted in 1999 and 2002. The study focuses on four institutions that relate fundamentally to the efficient operation of market incentives in an economy: (i) inter-enterprise competition and economic barriers to entry/exit, (ii) access to (regulated) utilities and infrastructure services, (iii) corporate governance, financial transparency and access to finance, and (iv) commercial dispute resolution. The methodological tools employed in the analysis investigate these institutions systematically across the eight SEE countries to allow for cross-country and cross-sectoral comparisons, and to develop a regional as well as a country-specific perspective on corresponding policy challenges. Chapter two presents an overview assessment of each of the four core issues of this study. It reviews in the aggregate the business environment in the eight countries, based on BEEPS (1 and 2) and the EBRD transition indicators. The remaining sections of this overview present a summary of the main findings of each of the four core chapters of the study: competition, regulated infrastructure utilities, corporate governance and finance, and commercial dispute resolution.